PENGELOLAAN ALOKASI DANA KAMPUNG DI KAMPUNG MEREMPAN HILIR KECAMTAN MEMPURA KABUPATEN SIAK TAHUN 2020 - Dian Hidayat; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is a research that is in the Field of Village Government System Studies. Village Funds are managed in an orderly manner, complying with the provisions of laws and regulations, efficient, economical, effective, transparent and responsible by paying attention to a sense of justice and compliance and prioritizing the interests of the community. The research approach is qualitative with descriptive analysis method by describing phenomena and data accurately. Primary sources of information (informants) were determined by purposive sampling and the necessary data were collected using interview techniques and literature study. The results of this study are ADK Management includes Planning, Implementation, Disbursement, Reporting and Control, Guidance, and Supervision. The management of ADK carried out by the Merempan Hilir Village Government has followed the technical guidelines that have been regulated in the legislation. However, the process is still not optimal. This can be seen from the delay in the reporting and disbursement processes. For the Reporting process for the Realization of the Use of ADK has not been in accordance with the predetermined schedule, causing delays in the disbursement of Funds for the next stage. Likewise with accountability for the use of ADK so that the community cannot evaluate the work of the village government and accountability to local governments is not carried out in a timely manner. Keywords: Management, Allocation, Village Fund